Subtypes of renal cell carcinoma with defined genomic alterations: diagnostic and prognostic significance. Issue 6 (June 2018) - Bonert, Michael; El-Shinnawy, Ihab
Abstract: The World Health Organization (WHO) 2016 classification of renal neoplasia defines renal cell carcinomas (RCCs) with genomic alterations: (1) succinate dehydrogenase deficient (SDH) RCC, (2) hereditary leiomyomatosis and renal cell carcinoma (HLRCC) syndrome-associated RCC and (3) the MiT family translocation carcinoma (Xp11 translocation carcinoma and t(6;11) carcinoma). Genomic alterations also define two syndromes associated with RCC that have a varied histology; tuberous sclerosis complex and Birt-Hogg-Dube. This review will examine the WHO entities and the two aforementioned syndromes, and discuss a genomic alteration (TCEB1 mutation) that appears to define a subset of clear cell RCCs that histomorphologically overlap with clear cell tubulopapillary RCC. The focus will be on diagnostic considerations from the pathologic perspective, and include discussion of clinical features, prevalence, prognosis, common and uncommon immunohistochemistical stains and molecular testing.